Genetically engineered CD80–pMHC-harboring extracellular vesicles for antigen-specific CD4+ T-cell engagement - Ishina, Irina A.; Kurbatskaia, Inna N.; Mamedov, Azad E.; Shramova, Elena I.; Deyev, Sergey M.; Nurbaeva, Kamila S.; Rubtsov, Yury P.; Belogurov, Alexey A.; Gabibov, Alexander G.; Zakharova, Maria Y. (Frontiers in Bioengineering and Biotechnology, 2024)
The identification of low-frequency antigen-specific CD4 + T cells is crucial for effective immunomonitoring across various diseases. However, this task still contains experimental challenges 2 This is a provisional file, not the final typeset article necessitating the implementation of enrichment procedures. While existing antigen-specific expansion technologies predominantly concentrate on the enrichment of CD8 + T cells, advancements in methods targeting CD4 + T cells have been limited. Here we report a technique, which harnesses antigenpresenting extracellular vesicles (EVs) for stimulation and expansion of antigen-specific CD4 + T cells. EVs are derived from a genetically modified HeLa cell line designed to emulate professional antigenpresenting cells (APCs) by expressing key costimulatory molecules CD80 and specific peptide-MHC-II complexes (pMHC). Our results demonstrate the beneficial potent stimulatory capacity of EVs for activating both immortalized and isolated from peripheral blood mononuclear cells (PBMC) human CD4 + T cells. Our technique successfully expands low-frequency Influenza-specific CD4 + T cells from healthy individuals. In summary, elaborated methodology represents a streamlined and efficient approach for the detection and expansion of antigen-specific CD4 + T cells, presenting a valuable alternative to existing antigen-specific T cell expansion protocols.